CITATION PRACTICES AMONGST TRAINEE TEACHERS AS REFLECTED IN THEIR PROJECT PAPERS - Shanmugam, Ambikapathi (Malaysian Journal of Library and Information Science, 2009)
The study aims to investigate errors in citation practices of postgraduate student teachers. This research examines the various types of citations according to bibliographic forms in relation to course options, language use and underlying reasons for the student teachers’ citation behaviors. The study involved 154 postgraduate student teachers from a Teacher Education Institution in East Malaysia. The citations used in a process based term paper submitted as part of their final course evaluation submitted to the Education Department were analyzed. Findings revealed that only 62.24% of the total population included a reference list in their assignment, and this was despite being provided with explicit instructions regarding the need to attach a reference page. From the total of 489 citations analyzed, 77.5 % were from text books. Materials from seminar papers and theses made up less than 3% of the total sources used. It was found that 3 most frequently cited authors accounted for a third of the total citations, and the authors were writers of the pedagogy text books used by the course lecturers. More than 83% of the sources employe were from local publications written in the Malay Language. The numbers of missing and inconsistent citations in the participants’ term papers were exceptionally high. Only 12.67% of the total citations were found to be correct. The trainees placed the blame on (a) lack of emphasis by course lecturers; and (b) ignorance of citation format leading to such errors. The findings suggest a need for deliberate and concerted efforts from course lecturers or teacher trainers to inculcate student teachers to accustom themselves to a variety of reference sources and instill a culture of avoiding citation errors. Exclusion of reference list in academic writing should not be tolerated as it has implications for the level of professionalism among trainees and their lecturers.